The Effect Quality of Service Consumer's for Purchasing Interest on Citilink Airlines at Halim Perdanakusuma International Airport Jakarta - Arif Fakhrudin (Politeknik Negeri Bengkalis, 2020)
Citilink Indonesia is a low-cost carrier that has a large number of enthusiasts. An increase in public purchasing interest for low-cost airlines, especially for Citilink, is certainly due to Citilink has different characteristics with other low-cost airlines, namely satisfying services. The purpose of this study is to determine whether quality of service affects consumers’ purchasing interest on Citilink Airlines at Halim Perdanakusuma International Airport, Jakarta. This study used data taken from a questionnaire distributed to Citilink customers, in this case passengers who have an official boarding pass from Citilink Airlines in the waiting area of the International Airport. Respondents in this study were service users consisting of 100 respondents. This data is then processed using the SPSS 15.0 program using Simple Linear Regression analysis. The results showed that H0 was rejected and H1 was accepted, which is indicated by F = 399,790 with a 0,000 <0.05, which means there is a significant effect of the quality of service on consumers’ purchasing interest at Citilink Airlines at Halim Perdanakusuma International Airport, Jakarta. The results of simple linear regression analysis using the SPSS program showed an effect of 80.3% which was shown by the Model Summary table and 19.7% was influenced by other factors